DIO1 Gene Polymorphism Is Associated with Thyroid Profiles and Reproductive Performance in Dairy Cows - Olga V. Kostyunina; Olga S. Mityashova; Nikolay V. Bardukov; Olga V. Aleynikova; Irina Y. Lebedeva (Agriculture, 2023)
Thyroid hormones mediate the interaction between the metabolic and reproductive systems, while their metabolism is controlled by different deiodinases. The present study aimed to search for associations of cow genotypes with SNPs in the deiodinase type 1 gene (DIO1) with thyroid profiles and reproductive traits. The blood was sampled from Russian black-and-white cows 2–6 weeks before calving and 1–13 weeks after calving to measure the hormonal levels by ELISA. RT-PCR analysis was performed for known mutations in the bovine DIO1 gene, and a polymorphism at position 13,149 was found. In animals with the CG genotype, the blood concentration of reverse triiodothyronine 6 weeks prepartum was higher and decreased much earlier than in animals with the CC genotype. Furthermore, 1 week after calving, the total triiodothyronine to reverse triiodothyronine ratio in cows with the CG genotype was higher than in cows with the CC genotype. A higher proportion of animals with better values of fertility traits was revealed in the CC group compared to the CG group. Thus, cows with the CC genotype of the DIO1 gene more often have a high reproductive ability, which may be associated with the rT3 profile features during the prepartum and early postpartum periods.